Pollution and Stunting (Case Study at DKI Jakarta) - Dudi Duta Akbar (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
Air pollution causes death, death due to illness, disability, or premature death in Jakarta. It is strongly associated with non-communicable diseases (NCDs), including chronic cardiovascular and respiratory diseases and lung cancer. Bad impact on human health. huge burden on the health sector and the country's economy. Children are at special risk from air pollution because of their organs, the relationship between air pollution and children's health and development has been proven. The impact of air pollution contributes to the prevalence of stunting. The results of this literature study found and at least estimated that air pollution has the potential to cause death, increased hospitalization due to cardio-respiratory diseases, and a greater increase in health problems, namely children every year in Jakarta. The total economic burden caused by air pollution is estimated at USD 2943.42 million (2.2% of its GDP) in 2019. Tracking provides the right evidence needed to guide city policy makers in prioritizing clean air actions to be taken to improve public health.